Results from a large targeted screening program for alpha-1-antitrypsin deficiency: 2003 - 2015. Issue 1 (December 2016) - Greulich, Timm; Nell, Christoph; Herr, Christian; Vogelmeier, Claus; Kotke, Viktor; Wiedmann, Stefan; Wencker, Marion; Bals, Robert; Koczulla, Andreas
Abstract Background Alpha-1-antitrypsin deficiency (AATD) is an autosomal codominant inherited disease that is significantly underdiagnosed. We have previously shown that the combination of an awareness campaign with the offer of free diagnostic testing results in the detection of a relevant number of severely deficient AATD patients. The present study provides an update on the results of our targeted screening program (German AAT laboratory, University of Marburg) covering a period from August 2003 to May 2015. Methods Diagnostic AATD detection test kits were offered free of charge. Dried blood samples were sent to our laboratory and used for the semiquantitative measurement of the AAT-level (nephelometry) and the detection of the S- or Z-allele (PCR). Isoelectric focusing was performed when either of the initial tests was indicative for at least one mutation. Besides, we evaluated the impact of additional screening efforts and the changes of the detection rate over time, and analysed the relevance of clinical parameters in the prediction of severe AATD. Results Between 2003 and 2015, 18, 638 testing kits were analysed. 6919 (37.12 %) carried at least one mutation. Of those, we identified 1835 patients with severe AATD (9.82 % of the total test population) including 194 individuals with rare genotypes. Test initiatives offered to an unselected population resulted in a dramatically decreased detection rate. Among clinical characteristics, a history of COPD, emphysema, and bronchiectasis were significant predictors for Pi*ZZ, whereas a history of asthma, cough and phlegm were predictors of not carrying the genotype Pi*ZZ. Conclusion A targeted screening program, combining measures to increase awareness with cost-free diagnostic testing, resulted in a high rate of AATD detection. The clinical data suggest that testing should be primarily offered to patients with COPD, emphysema, and/or bronchiectasis.